Implementation of the STEM project “modeling of spatial images of stellated Poyhedra” in the professional training of future vocational education teachers - Derevyanchuk, Oleksandr; Ridei, Nataliia; Tytova, Nataliia; Ravlyuk, Vasyl; Yatsko, Oksana (Edelweiss Applied Science and Technology, 2025)
In the context of rapid development of digital technologies and their integration into the educational process, the implementation of the STEM approach in teaching technical and natural sciences becomes particularly relevant. The combination of Science, Technology, Engineering, and Mathematics creates a powerful toolkit for developing practical skills and spatial thinking in future professional education teachers. Three-dimensional modeling of geometric figures is a prime example of an interdisciplinary approach, where mathematical concepts are implemented in a digital environment using modern technologies. For future professional education teachers, such an approach is particularly important as it allows them to develop technical skills and methodological competencies simultaneously. The article examines the theoretical foundations and practical aspects of implementing the STEM approach in the process of learning 3D modeling using the graphic editor AutoCad, as well as investigates the impact of this approach on the development of professional competencies of future specialists.